Peanut protein-polysaccharide hydrogels based on semi-interpenetrating networks used for 3D/4D printing. (April 2023) - Lin, Qianzhu; Hu, Yao; Qiu, Chao; Li, Xiaojing; Sang, Shangyuan; McClements, David Julian; Chen, Long; Long, Jie; Xu, Xueming; Wang, Jinpeng; Jin, Zhengyu
Abstract: The rise of 3D printing technology has made the personalization of food possible. In this study, peanut protein-polysaccharide semi-interpenetrating networks were constructed to improve the gelling and printing properties of composite hydrogels. The rheological and mechanical test results showed that the storage modulus and fracture stress of peanut protein composite hydrogels increased with increasing carrageenan and gellan gum concentrations. The storage modulus (G′) and hardness of the composite hydrogels with 1.5% polysaccharide addition reached above 10 4 Pa and 700 g, respectively. The thermal reversibility of both carrageenan and gellan gum gels meant that composite hydrogels could be created as recyclable printable edible inks for 3D food printing. In addition, the composite hydrogels were designed to change color in response to alterations in pH, which meant they could be used in 4D food printing applications, i.e., in situations where the ink changes its attributes sometime after printing. The results of this study should facilitate the rational design and fabrication of plant-based edible inks that can be used for the development of personalized foods with unique properties. Graphical abstract: Image 1 Highlights: Peanut protein-polysaccharide semi-interpenetrating network hydrogels were built. A recyclable food ink for 3D printing based on peanut protein hydrogels was prepared. Color response of the printed object to pH was realized by adding natural pigment. This study will contribute to the development of plant protein-based 3D printed food.